Rethinking of holistic knowledge of learner and of self in pedagogical content knowledge - Gunda, Janja M.; Alwi, Nor Hayati; Krauss, Steven Eric; Hamzah, Azimi (Impact Journals, 2016)
The component of knowledge of learner and of self is central in debated meaning of pedagogical contentknowledge (PCK) among researchers. Most studies have focused on transformative and integrative arrangements of othercomponents of PCK with agreed soul-body conflict view of learner, particularly in conventional contexts. Thisphenomenological study was conducted with two objectives in place: First, to address the prerequisites in conceptualisationof learner and of self. Second, it focused to unveil meaning of holistic knowledge of learner and of self. The sample of thisstudy involved five Muslim educators in Tanzania. Face to face interviews were used and later transcribed verbatim. Theresults reveal two main themes. The first theme is faith and spirituality with Divine Unity of Allah and unity of doubledimension of human life as its subthemes. The second theme is foundational holistic knowledge of learner and of self. Itssubthemes include mission and grand purpose of life, unified theory and practice, ingrained concept of am ā nah (Trust) andenthusiastic acceptance of being role model appeared as subthemes. Based on the research findings, it can be concludedthat Muslim educators need Islamic epistemological view and ideological skills of integrating belief in Allah and Hereafteras the constructive framework in rethinking for the foundational holistic knowledge of learner and of self in PCK.